2011
DOI: 10.1159/000324921
|View full text |Cite
|
Sign up to set email alerts
|

Mixture of Fibroblasts and Adipose Tissue-Derived Stem Cells Can Improve Epidermal Morphogenesis of Tissue-Engineered Skin

Abstract: Many studies demonstrate that the type of adjacent mesenchymal cells can affect epidermal morphogenesis of bilayered tissue-engineered skin. However, whether a mixture of different mesenchymal cell types can improve epidermal morphogenesis of bioengineered skin remains unknown. In this study, keratinocytes, dermal fibroblasts and adipose tissue-derived stem cells (ADSCs) were isolated and purified from human skin and subcutaneous fat. Conditioned medium generated from a mixture of dermal fibroblasts and ADSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 57 publications
4
27
0
1
Order By: Relevance
“…ADSCs used in this study were purchased commercially and showed typical mesenchymal stem cell characteristics, confirmed using multiple differentiation and flow cytometry analysis. The results were consistent with previous publications (Lu et al 2012;Zuk et al 2002).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…ADSCs used in this study were purchased commercially and showed typical mesenchymal stem cell characteristics, confirmed using multiple differentiation and flow cytometry analysis. The results were consistent with previous publications (Lu et al 2012;Zuk et al 2002).…”
Section: Discussionsupporting
confidence: 94%
“…Mesenchymal stem cell surface markers were confirmed for cultured ADSCs using fluorescence-activated cell sorting analysis for CD29 and CD44 (eBioscience, San Diego, CA, USA) according to the manufacturer's protocol. The induction of osteogenesis and adipogenesis were as previously reported (Lu et al 2012).…”
Section: Cell Culture and Characterizationmentioning
confidence: 86%
“…In support of paracrine action, keratinocyte and/or fibroblast proliferation, together with collagen transcription/synthesis by fibroblasts, can be enhanced using ASCconditioned medium or coculture systems [289][290][291]. Conditioned medium made from a mixture of ASCs and dermal fibroblasts can also increase keratinocyte proliferation and migration [292,293] and increased levels of HGF and KGF can be found in the media, suggesting a role for these factors [293]. Similar to this, stromal layers derived from human ASCs can induce the proliferation and expression of appropriate epidermal keratins when overlaid with keratinocytes, leading the authors to conclude that the ASC can be used to create a biomimetic stroma capable of stimulating epidermal development [136].…”
Section: In Vivo Ectoderm Regeneration-epithelial and Epidermalmentioning
confidence: 99%
“…ERK1/2 activation induced by mechanical force has been reported [Matsubayashi et al, 2004;Reichelt, 2007;Quaglino et al, 2009;Perera et al, 2010;Zhang et al, 2012]. However, whether mechanical stress can induce ERK1/2 activation in oral epithelial cells is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also showed that stromal cells and their matrices can influence upper epidermis development [Carriel et al, 2011;Lu et al, 2012]. Hence, RR elongation may result from the combination of all of the above mentioned aspects.…”
Section: Discussionmentioning
confidence: 99%